THE IMPACT OF INTEGRATED MARKETING COMMUNICATION ON CONSUMER PURCHASE DECISION AT HAWAI WATERPARK MALANG - Laksamana Virtuecrat (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aimed to determine the effect of Advertising (X1), Sales Promotion (X2), Interactive Marketing (X3), and Event Marketing (X4) on purchasing decision  (Y)  at  Hawai  Waterpark  Malang.  A  total  of  215  respondents  were selected on this study using purposive sampling techniques and methods of non- probability sampling by filling out a questionnaire that has been through the test validity and reliability to obtain data. Data were analyzed using multiple linear regressions. The analysis showed that, variable Advertising (X1), Sales Promotion (X2),  Interactive Marketing (X3), and Event  Marketing (X4) have significant influence   partially  on   purchasing   the   entrance/admission   ticket   to   Hawai Waterpark Malang, with Fcount 38.477 and significance 0,000. The results of this analysis suggest that, variable Advertising (X1) dominant influence by 43% in influencing purchasing decisions. Value Adj. R2 obtain the results for 0.412, which  means  the variable advertising  (X1),  sales promotion  (X2),  Interactive Marketing (X3), and event marketing (X4) is able to influence consumer purchase decisions  to  enter  Hawai  Waterpark  at  42.3%  and  the  remaining  57.7%  is explained by other factors not discussed in this study. Keywords:   Advertising,   Sales   Promotion,    Interactive   Marketing,   Event  Marketing, and Purchasing Decision.